2015
DOI: 10.3892/mmr.2015.3671
|View full text |Cite
|
Sign up to set email alerts
|

Selection of suitable reference genes for reverse transcription-quantitative polymerase chain reaction analysis of neuronal cells differentiated from bone mesenchymal stem cells

Abstract: Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) is a technique widely used for the quantification of mRNA transcription, It is well recognized that the reference genes used in RT-qPCR require appropriate validation to ensure that gene expression is unaffected by experimental conditions. The differentiation of bone mesenchymal stem cells (BMSCs) into neurons is important in the treatment of nerve injury. In gene expression analysis of the differentiation of BMSCs into neuronal cells by, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…These differences resulted from the heterogeneous gene expression profile of the tumor type, the experimental conditions, and the stability of the reference genes, being in agreement with the literature (Supplementary Table 1) [21,22,28,29]. In addition, the aforementioned variability can also be attributed to the different algorithms applied by the GeNorm and NormFinder [23,[30][31][32][33]. However, for the single HKG analysis, the first three ranked genes by GeNorm and NormFinder were the same ones, implying no substantial differences in their stability.…”
Section: Discussionsupporting
confidence: 87%
“…These differences resulted from the heterogeneous gene expression profile of the tumor type, the experimental conditions, and the stability of the reference genes, being in agreement with the literature (Supplementary Table 1) [21,22,28,29]. In addition, the aforementioned variability can also be attributed to the different algorithms applied by the GeNorm and NormFinder [23,[30][31][32][33]. However, for the single HKG analysis, the first three ranked genes by GeNorm and NormFinder were the same ones, implying no substantial differences in their stability.…”
Section: Discussionsupporting
confidence: 87%
“…In general, internal reference genes, such as 18S rRNA, GAPDH, and ACTB, are chosen for relative quantification analysis between clinical samples. However, increasing evidence has suggested that the expression levels of these commonly used internal reference genes are variable in distinct tissues, cell lines, between treatments of the same cell line (Ali et al, 2015; Ma et al, 2015; Yang et al, 2014; Yu et al, 2015), as well as across cell types (He et al, 2015; Li et al, 2015a; Li et al, 2015b). Thus, with the advancement of precise medicine, it is of high importance to evaluate and validate internal reference genes for the target gene expression profile studies among different cell types and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The complex spatial and temporal alterations after injury could further complicate interpretation of changes in gene expression (Gauthier et al, ; Yu and He, ). Therefore, reference genes that are frequently used for other experiments may be unsuitable for studies of neural development or regeneration (He et al, ). Although attempts have been made to search for reference genes in several other tissues, few studies have focused on reference genes in the developing brain and spinal cord from prenatal, postnatal to aging periods or under injury conditions.…”
Section: Introductionmentioning
confidence: 99%